Book Review: Handbook of Transport Geography and Spatial Systems (D. Hensher, K. Button, K. Haynes and P. Sopher (eds.)) - Meurs, Henk (European Journal of Transport and Infrastructure Research, 2006)
This is the fifth volume in the series ‘Handbooks in Transport’. The series is developed to be a reference work for researchers, practitioners and students within transport and logistics. In almost 700 pages this volume provides an overview of many geographical aspects of transportation. The editors aim at providing a useful manual or guidebook, especially for those who are unfamiliar within this area of work. In their introduction, the editors introduce some of their focal points within the book. They point at new technological changes, such as GIS, GPS and ITS which do have impacts on spatial systems, but which also can be of value in research (data collection and analysis). They point at the importance of institutional factors yielding the traditional disconnection between land use and transportation planning and hope that GIS may be an integrating factor. And they seem to be surprised that many urban areas still have no formal land use modelling capability.